Kesan Masa Pengeraman Nanozarah Zink Oksida yang Dihasilkan Menggunakan Afrons Gas Koloid = Incubation Effect on Zinc Oxide Nanoparticles Produced Using Colloidal Gas Aphrons - Saifful Kamaluddin, Muzakir; Shahidan, Radiman (Universiti Kebangsaan Malaysia, 2011)
Zinc oxide nanoparticles has been synthesized using colloidal gas aphrons as template. Zinc sulfate (ZnSO4.7H2O) and ammonia gas used as reactants. The incubation periods that have been studied are 2 h and 18 h. From the scanning electron microscope analysis, nanosheet morphology can be observed with thickness of 125 nm to 200 nm. From the UV-Vis spectroscopy analysis, the estimated average size for zinc oxide nanoparticles with 2 h incubation time is 2:03 nm and 2.1 nm for 18 h of incubation time.